Tremor and its duration‐amplitude distribution at Popocatépetl volcano, Mexico - R. Arámbula‐Mendoza; C. Valdés‐González; N. Varley; T. A. Reyes‐Pimentel; B. Juárez‐García (Geophysical Research Letters)
Abstract The duration‐amplitude distribution was calculated for the tremor observed at Popocatépetl volcano during episodes of activity in 2000 and 2012–2014. An exponential function was used to obtain a good fit for the duration‐amplitude distribution, and the source of volcanic tremor is probably generated by the transportation of magmatic fluids and its coupling with the host rock within the volcanic conduit. In particular, harmonic tremor has shown large amplitudes, durations, and mean values of amplitude, more than spasmodic or pulsating tremor. This is due to different generation mechanisms: in the case of harmonic tremor, it is produced during magma ascent and lava dome growth, while spasmodic and pulsating tremors are associated with fragmentation of the lava dome and gas emissions. This paper presents the duration‐amplitude distribution as a method to estimate the intensity of the tremor at Popocatépetl, a volcano with the major risk in all Mexico.